Media Education as a Necessary Component in Preparation of Future Mediacompetent Computer Science Teachers - Naumuk, Iryna (Pedagogical Discourse, 2015)
The article deals with the features of media education as a necessary component for media competence development for future computer science teachers. The importance of media education, media literacy and media competence that have many opportunities for students and for teachers is pointed out. As a result, the ability to assess information security, to use sources skillfully, to assess credibility, information correlation and knowledge and abilities to organize an information process are developed. The major forms of media education and the type of relationship between a teacher and a student and media in the modern information environment are highlighted. It is indicated that media education offers great opportunities, helping to develop the intellectual and creative potential, and to develop critical thinking. According to observation results the necessary conditions for the formation of media competence of future science teachers are determined. On the basis of generalization it is clear that practical range of media education is extremely wide and covers all the courses, consisting of the perception of image information (design, media products, etc.), application of mass media materials and training in creation of own texts. According to the results of the analyzed materials it is concluded that media education is a national and strategically necessary basis for the development of a society. The importance of media education and its aims for future computer science teachers training are emphasized. The importance of media competence development for increasing competence of computer science teachers in a society is mentioned. Media competence results in development of the ability to assess information security, to use sources skillfully, to verify the accuracy of data, information and knowledge correlation, the ability to organize an information process. Media technology has become such an important part of a modern society, that to know how to work with information is crucially important.